Online apologies to hotel guests in English and Japanese. (April 2020) - Morrow, Phillip R.; Yamanouchi, Kenta
Highlights: Replies to negative TripAdvisor reviews frequently include apologies. Rapport Management theory provides a useful framework for analyzing apologies. English and Japanese showed differences in the frequency/use of supporting strategies. Most apologies don't clearly take responsibility for service failure. Hotels apologize for guests' discomfort or unmet expectations, not service failure. Abstract: Although the speech act of apology has been extensively investigated, there has been relatively little research on apologies in Computer-Mediated Communication (CMC). The present study presents a comparative analysis of hotels' apologies to customers in English and Japanese CMC, drawing upon Spencer-Oatey's (2008) framework of rapport management. Data consisted of 200 responses by hotels to negative reviews on TripAdvisor. Rhetorical Move Analysis was used to identify Apologies and accompanying moves. Contrary to the perception that Japanese apologize more, results showed considerable similarity in the frequency of apologies and in the tendency to be unclear about accepting responsibility for service failure in English and Japanese. There was also similarity in the use of a corporate voice, but differences in the frequency and use of Explanation, Repair, Opening and Closing moves to enhance rapport.